2022
DOI: 10.1098/rsos.211926
|View full text |Cite
|
Sign up to set email alerts
|

Language of fungi derived from their electrical spiking activity

Abstract: Fungi exhibit oscillations of extracellular electrical potential recorded via differential electrodes inserted into a substrate colonized by mycelium or directly into sporocarps. We analysed electrical activity of ghost fungi ( Omphalotus nidiformis ), Enoki fungi ( Flammulina velutipes ), split gill fungi ( Schizophyllum commune ) and caterpillar fungi ( Cordyceps militaris ). The spiking characteristics are specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Thereby, we recorded the extracellular electrical potential in mushrooms and mycelium-colonised sub-strates as indicators of the fungi intrinsic activity. Action potential-like spikes of electrical potential have been observed using intra-cellular recording of mycelium of Neurospora crassa [20] and further confirmed in intra-cellular recordings of action potential in hyphae of Pleurotus ostreatus and Armillaria gallica [21] and in extra-cellular recordings of basidiocarps of and substrates colonised by mycelium of P. ostreatus [22], Ganoderma resinaceum [23], and Omphalotus nidiformis, Flammulina velutipes, Schizophyllum commune and Cordyceps militaris [24]. While the exact nature of the travelling spikes remains uncertain we can speculate, by drawing analogies with oscillations of electrical potential of slime mould Physarum poly-cephalum [25, 26, 27, 28], that the spikes in fungi are triggered by calcium waves, reversing of cytoplasmic flow, and translocation of nutrients and metabolites.…”
Section: Introductionmentioning
confidence: 84%
“…Thereby, we recorded the extracellular electrical potential in mushrooms and mycelium-colonised sub-strates as indicators of the fungi intrinsic activity. Action potential-like spikes of electrical potential have been observed using intra-cellular recording of mycelium of Neurospora crassa [20] and further confirmed in intra-cellular recordings of action potential in hyphae of Pleurotus ostreatus and Armillaria gallica [21] and in extra-cellular recordings of basidiocarps of and substrates colonised by mycelium of P. ostreatus [22], Ganoderma resinaceum [23], and Omphalotus nidiformis, Flammulina velutipes, Schizophyllum commune and Cordyceps militaris [24]. While the exact nature of the travelling spikes remains uncertain we can speculate, by drawing analogies with oscillations of electrical potential of slime mould Physarum poly-cephalum [25, 26, 27, 28], that the spikes in fungi are triggered by calcium waves, reversing of cytoplasmic flow, and translocation of nutrients and metabolites.…”
Section: Introductionmentioning
confidence: 84%
“…Similar to the scientists aiming to create a standard model for plant signals, some researchers are going so far as to compare the electric responses of fungi to language, where different patterns of electric potential spikes represent different words. The fungi studied exhibited lexicons of up to 50 words, but the core lexicon which appeared most frequently did not exceed 15-20 words [18]. The researchers found that the distribution of the length of the spike in the spike trains corresponded to the distribution of word lengths of human languages.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we recorded the extracellular electrical potential in mushrooms and mycelium-colonized substrates as indicators of the fungi intrinsic activity. Action potential-like spikes of electrical potential have been observed using intra-cellular recording of mycelium of Neurospora crassa [ 20 ] and further confirmed in intra-cellular recordings of action potential in hyphae of Pleurotus ostreatus and Armillaria gallica [ 21 ] and in extra-cellular recordings of basidiocarps of and substrates colonized by mycelium of P. ostreatus [ 22 ], Ganoderma resinaceum [ 23 ], and Omphalotus nidiformis, Flammulina velutipes, Schizophyllum commune
Figure 1. Experimental setup.
…”
Section: Introductionmentioning
confidence: 86%